Interactions between N, P in the overlying water and flooding-induced decomposition of Cynodon dactylon in the water-level fluctuation zone - Huang, Jitao; Luo, Ze; Xu, Zuopeng; Jiang, Yanxue; Guo, Jinsong (Frontiers in Plant Science, 2025)
During flooding in the Water Level Fluctuation Zone (WLFZ), nutrient levels of nitrogen (N) and phosphorus (P) in the overlying water fluctuate due to soil nutrient release, impacting the decomposition of plants like Cynodon dactylon. However, limited research on the effects of these nutrient changes on plant nutrient release and water dynamics complicates accurate assessments of water quality impacts. This study used 8 water samples with varying initial nutrient levels to simulate N and P changes induced by WLFZ soil nutrients and examined the decomposition and nutrient dynamics of Cynodon dactylon. Results showed that flooding significantly increased initial levels of N and P, especially as particulate nitrogen (PN) and particulate phosphorus (PP), affecting both plant decomposition and nutrient dynamics in the water. After 60 days, Cynodon dactylon lost 47.97%-56.01% dry matter, 43.58%-54.48% total nitrogen (TN), and 14.28%-20.50% total phosphorus (TP). Initial PN and total dissolved nitrogen (TDN) promoted dry matter loss, PN and PP promoted TP loss, while PN and TDN inhibited TN loss. By day 60, no positive correlation was found between plant-released N and P and TN or TP in the overlying water. However, initial PP and PN levels were negatively correlated with TN and TP, indicating an inhibitory effect. Further analysis indicates that PN and PP released from the soil supported the formation of microbial aggregates, enhancing denitrification and phosphorus removal and thus improving water purification over time.